1971
DOI: 10.1021/jm00291a003
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic amino acid hydroxylase inhibitors. 2. 3-Alkyl-.alpha.-methyltyrosines

Abstract: 3-Iodotyrosine is a potent inhibitor of tyrosine hydroxylase in vitro, but lacks significant in vivo activity due to deiodination and transamination. On the basis of previous studies with thyroxine analogs, a series of 3-alkyl-amethyltyrosines was synthesized. A 3-Me, Et, or f-Pr substituent was found to have little effect on the tyrosine hydroxylase inhibitory property of -methyltyrosine. A 3-ieri-Bu group, however, caused a marked decrease in inhibitory activity.Numerous attempts have been made to modify tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The benzyl group was introduced by reaction with 2,4-di-tert-butyl-2-hydroxy benzaldehyde in the presence of potassium carbonate using DMF to give 3 as the product. A similar type of reaction has been reported by Counsell and co-workers in the synthesis of di-substituted 1-phenol-2-propanones, 56 and by Belmar and Jiménez for preparing hindered polyanionic chelating ligands. 57 Crystals of 3 were grown from hexane by evaporation; the structure elucidated is shown in Figure 3.…”
Section: Pendent Arm Synthesissupporting
confidence: 63%
“…The benzyl group was introduced by reaction with 2,4-di-tert-butyl-2-hydroxy benzaldehyde in the presence of potassium carbonate using DMF to give 3 as the product. A similar type of reaction has been reported by Counsell and co-workers in the synthesis of di-substituted 1-phenol-2-propanones, 56 and by Belmar and Jiménez for preparing hindered polyanionic chelating ligands. 57 Crystals of 3 were grown from hexane by evaporation; the structure elucidated is shown in Figure 3.…”
Section: Pendent Arm Synthesissupporting
confidence: 63%
“…Also shown is the 2-hiscarboxylate triad anchoring the active site iron. of Udenfriend [122][123][124][125], Counsell [42,[126][127][128] and others was that the inhibition of TH, catalyzing the rate-limiting step in norepinephrine biosynthesis, would lead to a decrease in vascular tone and thus function as an antihypertensive therapy. Halogenated derivatives of phenylalanine were discovered to be potent inhibitors of both TH and PAH in vitro, with preferential inhibition of TH by the metahalogenated compounds [126].…”
Section: The Iron Sitementioning
confidence: 99%
“…The halogenated analogs lack significant in vivo activity because they are rapidly destroyed by dehalogenases and transaminases [129]. Several compounds with alkyl groups attached to the meta position of the ring in α-methyltyrosine were also synthesized and found to inhibit TH [42,46]. The strong affinity for the chloro-probe in the vicinity of the metaposition of L-Tyr indicated that this area has a strong affinity for halogens and explains the preferential inhibition of TH for these compounds (Fig.…”
Section: The Iron Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Syntheses of these hydrazides have been described previously. 7 Pharmacological Results. Acute Toxicity.…”
mentioning
confidence: 99%